Life cyle assessment of activated carbon from waste materials as an adsorbent in wastewater treatment - Dayang Nurzafirah Hazirah Awg Razak,; Norashikin Ahmad Kamal,; Lee, Gooyong (Penerbit Universiti Kebangsaan Malaysia, 2024)
Activated Carbon (AC) has been a great alternative to reduce the cost of the process in wastewater treatment plants (WWTP) but they also have several hidden impacts on the environment. The impact assessment on the waste materials from coconut shells and wood will be identified using the Life Cycle Assessment (LCA) software approach. Through the “Cradle-to-gate” approach, activated carbon made from waste materials is produced and consumed, and its eighteen environmental effects which are fine particulate matter formation, fossil resource scarcity, freshwater ecotoxicity, freshwater eutrophication, global warming, human carcinogenic toxicity, human non-carcinogenic toxicity, ionizing radiation, land use, marine ecotoxicity, marine eutrophication, mineral resource scarcity, human health, terrestrial ecosystem, stratospheric ozone depletion, terrestrial acidification, terrestrial ecotoxicity and water consumption are assessed using the LCA software. This study aims to discover whether the choice of waste material precursors from the Activated Carbon (AC) can help to minimise environmental impacts. The study evaluates the potential benefits of using waste-derived activated carbon in wastewater treatment by comparing the environmental performance of activated carbon obtained from coconut, wood, and coal. This study is based on past studies all around the world. In thirteen of the eighteen impact categories, wood has the greatest environmental impact. Coconut shells on the other hand, has the lowest total environmental impacts, ranking first or second in fifteen among the eighteen environmental categories. The findings help in making choices for environmentally friendly wastewater treatment methods by illuminating the effects of employing waste products as an alternative source of adsorbents.